Intrauterine activation of the fetal immune system in response to maternal COVID-19 - N. R. Gashimova; L. L. Pankratyeva; V. O. Bitsadze; J. Kh. Khizroeva; N. A. Makatsariya; M. V. Tretyakova; A. S. Shkoda; K. N. Grigoreva; V. I. Tsibizova; J.-C. Gris; F. E. Yakubova; D. V. Blinov; et al. (Акушерство, гинекология и репродукция, 2023)
Introduction. During pregnancy COVID-19 poses a serious threat to both maternal health and health of paired unborn child. Pregnant women have a high probability of complications due to respiratory viral infections followed by developing critical conditions caused by physiologically altered immune and cardiopulmonary systems. However, asymptomatic COVID-19 in pregnant women may be accompanied by fetal inflammatory response syndrome (FIRS) that results in unfavorable sequelae for neonatal life and health.Aim: to assess a fetal inflammatory response resulting from maternal COVID-19 in pregnancy.Materials and Мethods. A prospective randomized comparative study involving 92 pregnant women was carried out. The main group included 62 pregnant COVID-19 convalescent women: subgroup 1 consisted of 30 pregnant women found to be positive for SARS-CoV-2 by using polymerase chain reaction (PCR) 4–6 weeks before delivery; subgroup 2 – 32 pregnant women with SARS-CoV-2 detected by PCR earlier during pregnancy. The control group enrolled 30 healthy pregnant women. The level of circulating cytokines – interleukins (IL) IL-1α, IL-6, IL-8, IL-10, granulocyte-macrophage colony-stimulating factor (GM-CSF), tumor necrosis factor alpha (TNF-α), interferon gamma (IFN-γ), macrophage inflammatory protein-1β (MIP-1β), C-X-C motif chemokine ligand 10 (CXCL-10) and cell markers (CD86, CD80, CD4, CD25, CD25, CCR7) were analyzed. In addition, all neonates underwent thymus gland ultrasound screening.Results. Cord blood dendritic cells from neonates born to mothers in subgroup 1 vs. control group showed a significantly upregulated expression of CD80 and CD86 (p = 0.023). Moreover, such cord blood samples in subgroup 1 were found to have increased percentage of CD4+, CCR7+ T cells paralleled with decreased proportion of naive CD4+ T cells as compared with control group (p = 0.016). It was found that count of maternal regulatory CD4+CD25+Foxp3+ T cells (Treg) did not differ significantly, whereas Treg cell functional activity in mothers with severe COVID-19 (subgroup 2) was significantly suppressed. Significantly higher level of neonatal proinflammatory cytokines and chemokines was detected in subgroup 1 vs. control group (p < 0.05). However, the cytokines level in maternal peripheral blood samples in main and control groups upon delivery was changed insignificantly. SARS-CoV-2-positive pregnant women showed a strong antigen-specific T cell response. A reduced thymus size was found in neonates born to paired COVID-19 mothers.Conclusion. Fetal inflammatory response syndrome occurs upon COVID-19, which is characterized by activated fetal immune system and increased production of pro-inflammatory cytokines. The disease severity in pregnant women has no correlation with FIRS intensity during neonatal period and can vary from minimally altered laboratory parameters to developing sequelae at organ and body system levels.